Automatic Failure Explanation in CPS Models - Bartocci, Ezio; Manjunath, Niveditha; Mariani, Leonardo; Mateis, Cristinel; Ničković, Dejan (Lecture notes in computer science, 2019)
Debugging Cyber-Physical System (CPS) models can be extremely complex. Indeed, only detection of a failure is insufficient to know how to correct a faulty model. Faults can propagate in time and in space producing observable misbehaviours in locations completely different from the location of the fault. Understanding the reason of an observed failure is typically a challenging and laborious task left to the experience and domain knowledge of the designers. In this paper, we propose CPSDebug, a novel approach that combines testing, specification mining, and failure analysis, to automatically explain failures in Simulink/Stateflow models. We evaluate CPSDebug on two case studies, involving two use scenarios and several classes of faults, demonstrating the potential value of our approach.